Modeling and simulations of ultra-intense laser-driven bremsstrahlung with double-layer targets. (1st April 2022) - Formenti, A; Galbiati, M; Passoni, M
Abstract: High-energy bremsstrahlung emission can occur owing to electron scattering in the nuclei or ions Coulomb field following the relativistic-electron generation in high-intensity laser interaction with plasmas. Such emission of photons in the keV–MeV energy range is of interest to characterize the relativistic-electron populations and develop laser-based photons sources. Even if it is a well-established and widely studied emission process, its modeling in laser-plasma scenarios needs further investigation. Moreover, advanced near-critical double-layer targets (DLTs), consisting in a low-density foam deposited on a thin solid substrate, have never been explored extensively for bremsstrahlung photon emission. Therefore, in this paper, we show the rationale, advantages, limitations, application regime, and complementarity of different modeling approaches and apply them to the unconventional configuration based on DLTs. We use multi-dimensional particle-in-cell (PIC) simulations coupled with a Monte Carlo strategy to simulate bremsstrahlung in two ways: integrated into the PIC loop itself or after the simulation with two separate codes. We also use simplified semi-analytical relations to retrieve the photon properties starting only from information on the relativistic electrons. With these tools, we investigate bremsstrahlung emission when an ultra-intense laser (0.8 µ m wavelength, 30 fs duration, a 0 = 20 and 3 µ m waist) interacts with DLTs having different properties. Despite some limitations of the numerical tools, we find that all approaches significantly agree on the characteristics of 1–100 MeV photon emission. This points to the possibility of adopting the different modeling approaches in a complementary way while at the same time identifying the best suited for a specific scenario. Regardless, DLTs appear to overall boost the high energy photon emission while at the same time enabling control of the emission itself.